Experiences of caregivers with spouses receiving chemotherapy for colorectal cancer and their expectations from nursing services - Ayse Cal; Ilknur Aydin Avci; Figen Cavusoglu (Elsevier, 2017)
Objective: The purpose of this study was to reveal experiences of caregivers whose spouses were receiving chemotherapy for colorectal cancer and their expectations from nursing services. Methods: This is a qualitative study. The caregivers were interviewed at their home. Sampling criteria were volunteering to participate in the study, being able to understand Turkish, not having speech or hearing problems and offering care to spouses with primary colorectal cancer. The interviews continued until concepts likely to be responses to research questions repeatedly appeared. Fourteen caregivers with spouses receiving chemotherapy for colorectal cancer comprised the study sample. Data were collected with a descriptive characteristics form and a semi-structured interview at in-depth interviews after making appointments with the caregivers on the phone. The steps followed in the content analysis were coding data, an organization of codes and themes, description of findings and evaluation of findings. Results: Experiences of the caregivers whose spouses were receiving chemotherapy for colorectal cancer and their expectations from nursing services were found to comprise the following themes "Facing the Disease," "Difficulties Encountered," "Continuing to Live," and "Provision of Health Care Services." Conclusions: The results of the study revealed that cancer and its treatment affected not only cancer patients but also their spouses offering care. Nurses giving care at oncology clinics, public health centers, and home can make care plans based on the four themes emerging in this study and can detect problems earlier and create appropriate solutions to them. They will contribute to the literature revealing needs of people offering care to oncology patients as well.